Structural and Magnetic Investigation of the Ferromagnetic ZnO:Co Nanotubes Fabricated by Electrophoretic Deposition Method - Li, Jianjun; Zhu, Jinbo; Zhang, Liting; Liu, Yin; Hao, Weichang (Asian Journal of Chemistry, 2013)
Zn1-xCoxO nanotubes (x = 0.01-0.07) have been controllable synthesized by electrophoretic deposition method using anodic aluminum oxide (AAO) as template. Careful structural characterization indicates that the prepared nanotubes are of poly-crystal wurtzite structure and composed with 8-15 nm nano-crystals. Magnetic investigation indicates the obtained nanotubes are of room-temperature ferromagnetic and the magnetism increases with the increase of Co doping. The magnetism of the nanotubes is much higher than that of the nanowires with similar dose of Co doping. Careful study indicates this difference of the magnetism is due to the surface-preferential Co distribution resulted by the electrophoretic deposition process.